A qualitative case study of employee turnover in retail business - Omotayo Olubiyi; Garrett Smiley; Henry Luckel; Ralph Melaragno (Heliyon, 2019)
This study on the person-organization fit theory, measured in terms of value congruence, explored qualitative data from a survey of non-managerial retail employees in a Northwestern state in the United States in relation to job satisfaction and employee-organization value congruence in a retail establishment that has shown a remarkable deviation from the norm with employee turnover far below what is obtainable in the retail industry. The results of a field study of 18 employees, through open ended interviews and survey transcripts, analyzed thematically using Nvivo qualitative data analysis tool, identified five themes that influence job satisfaction and employee retention: Friendly workplace environment, Flexibility, Stability, Management Support, and Independence.